Conservation actions for restoring the coastal lagoon habitats: Strategy and multidisciplinary approach of LIFE Lagoon Refresh - Boscolo Brusà, Rossella; Feola, Alessandra; Cacciatore, Federica; Ponis, Emanuele; Sfriso, Adriano; Franzoi, Piero; Lizier, Matteo; Peretti, Paolo; Matticchio, Bruno; Baccetti, Nicola; Volpe, Valerio; Maniero, Luigi; et al. (Frontiers in Ecology and Evolution, 2022)
The Habitat Directive of European Union lists Costal Lagoons (habitat code 1150*) among priority habitat because they are in danger of disappearance. Natural ecosystems may recover from anthropogenic perturbations; however, the recovery can follow natural restoration or it can be redirected through ecological restoration by anthropogenic intervention. Accordingly with collecting the available theoretical indications for restoration of estuarine and coastal areas, a methodological approach was detailed. It can be summarized into five issues: i) Environmental context from which it began; ii) Desired state to be achieved; iii) Policies and socio-economic context; iv) Typology of recovery and/or improvement of habitats and ecosystems and v) Methods for monitoring the impact of the project. The project strategy, management and measures of LIFE Lagoon Refresh were also presented and discussed, as a case study for the implementation of the multidisciplinary approach for restoration ecology in transitional waters. The project take place in the northern Venice Lagoon (Italy), started in 2017 and it lasts 5 years. In Venice Lagoon, since the 20th century, a strong reduction of the typical salinity gradient of buffer areas between lagoon and mainland and of reedbed extension has occurred due to historic human interventions, with negative consequences on coastal lagoon habitat. To improve the conservation status of habitats and biodiversity of the area, the LIFE Lagoon Refresh project included several conservative actions. These included the diversion of a freshwater flow from the Sile River into the lagoon; the restoration of intertidal morphology, through biodegradable structures; the reed and aquatic angiosperm transplantations with the involvement of local fishermen and hunters, and the reduction of hunting and fishing pressures in the intervention area. To achieve the restoration of the lagoon environment, the strategy of the project covered a combination of different aspects and tools. These included planning activities, through the involvement of local Institutions and communities; stakeholder’s involvement to increase awareness of environment conservation and socioeconomic value improvement; an ecological engineering approach; numerical models as supporting tool for planning and managing of conservation actions; environmental monitoring, performed before and after the conservation actions.